(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Hypertension is both a cause and a consequence of renal parenchymal disease. Once detected, formulation of an appropriate therapeutic strategy is imperative to not only control hypertension, but also to retard the progression of the renal pathology. Judicious and optimal use of the available antihypertensive agents is of utmost importance. This study aims at analyzing the influence of current guidelines on prescribing in this particular subset of patients. Case history of patients having hypertension comorbid with renal pathological disorders was noted down from the medical records department. A total of 58 prescriptions thus noted were analysed on the basis of antihypertensive agents that were prescribed. The CCB’s were the group of drugs prescribed the most in renal disease associated hypertension (79%) followed by the diuretics (48%).The ACE‐inhibitors and ARB’s were prescribed in around 34% of the patients. Amlodipine and Frusemide were the most frequently used individual agents.